Ca-looping for postcombustion CO2 capture: A comparative analysis on the performances of dolomite and limestone. (15th January 2015) - Valverde, J.M.; Sanchez-Jimenez, P.E.; Perez-Maqueda, L.A.
Graphical abstract: Calcined dolomite with superior Ca-looping performance for CO2 capture. Highlights: The CO2 capture performance of dolomite is studied at realistic calcium-looping conditions. Dolomite has a superior capture performance as compared to limestone. MgO grains in decomposed dolomite serve as a thermally stable support for CaO. Full decarbonation of dolomite is achieved at lower calcination temperatures as compared to limestone. Abstract: The low cost and wide availability of natural limestone (CaCO3 ) is at the basis of the industrial competitiveness of the Ca-looping (CaL) technology for postcombustion CO2 capture as already demonstrated by ∼ 1 Mw t scale pilot projects. A major focus of studies oriented towards further improving the efficiency of the CaL technology is how to prevent the gradual loss of capture capacity of limestone derived CaO as the number of carbonation/calcination cycles is increased. Natural dolomite (MgCa(CO3 )2 ) has been proposed as an alternative sorbent precursor to limestone. Yet, carbonation of MgO is not thermodynamically favorable at CaL conditions, which may hinder the capture performance of dolomite. In the work described in this paper we carried out a thermogravimetric analysis on the multicyclic capture performance of natural dolomite under realistic regeneration conditions necessarily implying high calcination temperature, high CO2 concentration and fast transitions between the carbonation and calcination stages. Our study demonstrates that the sorbent derived from dolomite has a greater capture capacity as compared to limestone. SEM analysis shows that MgO grains in the decomposed dolomite are resistant to sintering under severe calcination conditions and segregate from CaO acting as a thermally stable support which mitigates the multicyclic loss of CaO conversion. Moreover, full decomposition of dolomite is achieved at significantly lower calcination temperatures as compared to limestone, which would help improving further the industrial competitiveness of the technology.